Prolonged Methylprednisolone Therapy in the Fibro-Proliferative Phase of Acute Respiratory Distress Syndrome - CEYHAN, BERRİN; ÇELİKEL, ÇİĞDEM; KOCAKAYA, DERYA; OLGUN YILDIZELİ, ŞEHNAZ (CUREUS INC, 2021)
Late-stage acute respiratory distress syndrome (ARDS), primarily associated with fibro-proliferative changes, may occur in many patients. This stage, where ARDS progresses to the point of being incurable, involves a complicated and long clinical course that may give rise to functional loss; it has therefore been a major focus of both preventive and therapeutic strategies. In the present case report, the successful use of prolonged methylprednisolone therapy in the fibre-proliferative phase of ARDS is described in a patient who developed pneumonia and secondary ARDS after terminating a pregnancy due to preeclampsia. Methylprednisolone therapy, which was initiated at a daily dosage of 1mg/kg, was tapered down based on the clinical and radiologic status of the patient and was terminated at the end of the sixth month. Follow-up imaging studies and pulmonary function tests performed at the end of the first and sixth months showed marked improvements and the patient experienced no systemic adverse effects despite long-term steroid therapy.
Keywords: prolonged methylprednisolone therapy; acute respiratory distress syndrome; respiratory distress syndrome; methylprednisolone; pulmonary fibrosis; ARDS; CORTICOSTEROIDS; MECHANISMS; OUTCOMES